Early detection of myocardial involvement by non-contrast T1ρ mapping of cardiac magnetic resonance in type 2 diabetes mellitus - Shu, Hongmin; Xu, Huimin; Pan, Zixiang; Liu, Yan; Deng, Wei; Zhao, Ren; Sun, Yan; Wang, Zhen; Yang, Jinxiu; Gao, Hui; Yao, Kaixuan; Zheng, Jie; et al. (Frontiers in Endocrinology, 2024)
Objective: This study aims to determine the effectiveness of T1ρ in detecting myocardial fibrosis in type 2 diabetes mellitus (T2DM) patients by comparing with native T1 and Extracellular volume (ECV) fraction. Methods: T2DM patients (n=35) and healthy controls (n=30) underwent cardiac magnetic resonance. ECV, T1ρ, native T1, and global longitudinal strain (GLS) values were assessed. Diagnostic performance was analyzed using receiver operating curves. Results: The global ECV and T1ρ of T2DM group (ECV = 32.1±3.2%, T1ρ = 53.1±2.0 msec) were significantly higher than those of controls (ECV = 26.2±1.6 %, T1ρ = 51.6±3.8 msec) (all P < 0.001), whether there was no significant difference in native T1 between T2DM and controls (P = 0.264). The GLS decreased significantly in T2DM patients compared with controls (-16.5±2.4% vs. -18.3±2.6%, P = 0.015). The T1ρ and native T1 were associated with ECV (Pearson’s r = 0.50 and 0.25, respectively, both P < 0.001), the native T1, T1ρ, and ECV were associated with hemoglobin A1c (Pearson’s r = 0.41, 0.52, and 0.61, respectively, all P < 0.05), the ECV were associated with diabetes duration (Pearson’s r = 0.41, P = 0.016). The AUC of ECV, T1ρ, GLS, and native T1 were 0.869, 0.810, 0.659, and 0.524, respectively. Conclusion: In T2DM patients, T1ρ may be a new noncontrast cardiac magnetic resonance technique for identifying myocardial diffuse fibrosis, and T1ρ may be more sensitive than native T1 in the detection of myocardial diffuse fibrosis.